Estudio de las estrategias comunicacionales vinculadas al periodismo ecológico, en la reserva natural La Ceiba del cantón Zapotillo, provincia de Loja y su influencia en la creación de una conciencia ambiental periodo septiembre 2012 - agosto 2013. Propuesta alternativa - Calva Sarango, Karen Elizabeth (2014)
It is unavoidable to stand out the importance and responsibility that have the Media in the society, being one of their purposes the service to the community, in the different ones problematic that you/they suffer to the citizenship. Hence, the work consists on the "STUDY OF THE COMMUNICATIVE STRATEGIES LINKED TO THE ECOLOGICAL JOURNALISM, IN THE NATURAL RESERVE THE CEIBA OF THE ZAPOTILLO CANTON, LOJA’S PROVINCE, AND THEIR INFLUENCE IN THE CREATION OF AN ENVIRONMENTAL CONSCIENCE. PROPOSAL ALTERNATIVE." .In the investigation methods were included like; deductive, inductive, analytic, descriptive, statistical, analysis of results, conclusions, recommendations and an alternative proposal. The sample with which one worked it was a total of 372 people, belonging to the Zapotillo canton. The main objective was to determine the incidence of the mass media in the generation of environmental conscience that search the preservation of the area. After the investigative process, it was evidenced the necessity the diffusion and formation that it motivates people to value the environmental near problem and their capacity to contribute in its. Key words: Mass media strategies, Ecological Journalism, Natural Reserves the Ceiba, Environmental conscience, Diffusion and information.